Physical, physicochemical, microbiological, and bioactive compounds stability of low-calorie orange jellies during storage: packaging effect (Research, Society and Development, 2020)
Fruit jellies are widely produced as a way to utilize fresh fruits, which are highly perishable. Orange a fruit widely consumed in Brazil, it has a significant amount of bioactive compounds. Despite the great progress in the development of jellies, several factors can change its useful life, among them is the packaging. Therefore, the objective of this study was to evaluate the effect of packaging on the physicochemical, physical, microbiological and bioactive compounds stability of low-calorie orange jellies during storage. Analyses every 30 days during the 180 days of storage. The results showed that increased storage time led to a decrease in pH, reduction of the flow rate (polypropylene packaging), reduction in yellow intensity, and growth of fungi and yeasts (higher in polypropylene packaging). In contrast, luminosity, red intensity, moisture, total sugars, and the consistency index tended to remain stable during storage. The DPPH results showed an increase in the antioxidant activity and reduction of vitamin C throughout the period of storage, especially in polypropylene packaging. The total phenolic content was stable with a tendency to decrease during storage. Notably, vitamin C showed a positive correlation with antioxidant activity in jellies. Low-calorie orange jellies packaged in glass showed the least changes during storage.